(untitled) (Archives of Criminology, 1991)
The paper shows various approaches to the perpetrator of crime, and practical consequences of the specific point of view adopted. The object is not to point to ready solutions or to declare for or against the discussed views, but to give an outline of the variety of problems that concern the person of offender, and to mention the related questions and issues. Discussed have been the general theoretical problems related to the person of offender; psychological problems; those arising from the fact that the offender has been made subject of criminological research; and the problems of the image of offender functioning in public opinion. Whether we formulate criminological theories or adopt definite practical solutions, questions cannot be avoided about the offender as a human being, about his rights, the extent of his freedom and responsibility, his relationship with society, and the limits of a just and permissible intervention in those rights and liberties. The problems mentioned in this relation point to the need for the problems of offender to be considered in a broad philosophical perspective based on a moral reflection. The discussion of psychological problems is focused on two issues. The first of them are the psychological conceptions of man which provide explanations of the offender’s criminal behaviour and lead to conclusions as to the treatment of offenders. Those problems have been exemplified by behaviourist and psychoanalytical ideas and the conception of humanistic psychology. Another important psychological problem is whether the offender’s behaviour that violates the legal norms results from his personality traits or has been conditioned by the situation in which he found himself. Studies point to complexity of this problem and to the fact that both personality and situation influence criminal behaviour. At the same time, some individuals are particularly resistant and others particularly susceptible to situations conducive to that behaviour. There are also situations in which an offence is particularly easily committed. Among them, there are the rapid changes found during great historic events and social transformations, as well as the situations, most and sotimes even extremely difficult, created by socio-political systems. In some offences, situation is a most important factor; in others the offender’s personality plays a greater part. This complexity of the problem should be taken into account when deciding about a given offender in the practical operation of criminal justice. The image of offender obtained in criminological studies of convicted persons is connected with a variety of problems. Some of tchem arise from the very definition of offender. It is a most general notion, related to the legislation in force in a given country at a given moment, and designating perpetrators of a great variety of acts which may result from different situations and psychological mechanisms. A question arises whether a single act, possibly jus an episode, may really constitute a good criterion to distinguish a given individual from others who have not committed such an act: whether that act is an isolated event only or results from the given person’s way of living. What also matters for the picture of a convicted offender obtained in studies is the process of selection to which he had been subjected before the offence was revealed, criminal proceedings instituted, and the offender convicted. A factor essential for that selection, for decisions concerning the offender, and for his readaptation to life in society after release is the stereotype of offender which functions in public opinion. As shown by studies, that stereotype is shaped by fear and the thirst for revenge on a person who is perceived as a threat but at the same time treated as a distant stranger. A condemnation of certain acts makes the Public realize the noxiousness of those acts and shapes moral attitudes. But the condemnation of acts does not have to lead to a similar disapproval of their perpetrators. It is most necessary to conduct criminological research and to provide society with straightforward information about the findings.